Rural Indigenous entrepreneurship: Emerging Field in Iranian Rural Research - Ali Akbar Anabestani; Mehrshad Toulabi Nejad (تحقیقات کاربردی علوم جغرافیایی)
Rural indigenous entrepreneurship is one of the youngest research areas to show that in Iran, one of the largest countries in Asia and has rich cultural heritage and indigenous communities, the issue of native rural entrepreneurship has not been addressed so far. Therefore, the present article, as an analytical assessment and with a variety of approaches based on richness and conceptual diversity in the fields of social sciences, economic, planning and rural development, uses a systematic approach, while introducing entrepreneurship while introducing entrepreneurship. Rural native to introduce native rural entrepreneurship to the context of future research in the country. This article contributes to a comprehensive understanding of native entrepreneurship research by analyzing literature and research lines. In this regard, the present article, which is intended for the purpose and information provided by the documentary method, sought to answer the questions about what elements of the difference between native rural entrepreneurship and classical entrepreneurship? What are the unique goals and characteristics of rural native entrepreneurship? And what are the (model) pattern for the development of native rural entrepreneurship in Iran? The results of the study indicate that indigenous entrepreneurship is different from classical/ Western entrepreneurship, and emphasizes elements such as the use of indigenous resources, indigenous cultural values, collective interest, family relationships and family/ family ties. The results showed that rural native entrepreneurship is not necessarily in response to market needs and is mostly aimed at providing family livelihoods, environmental protection, cultural and spiritual value. Unlike Western-style entrepreneurship, rural native entrepreneurship shows elements of equality-equality, collective/kinship activity, and emphasis on available cultural values ​​and natural resources. Rural indigenous entrepreneurship is often carried out with intra -household livelihoods and mostly with non -economic goals such as preserving livelihoods, preserving indigenous culture, protecting the environment and spiritual goals.